Технология настройки имитационной модели процессов развития региональной макроэкономической системы - Гринченко, Марина Анатольевна; Бабич, Игорь Игоревич (Технологический центр, 2012)
В статье предложена технология настройки имитационной модели региональной макроэкономической системы. В рамках предложенной технологии разработаны методика построения функций, отражающих причинно-следственные связи в модели, методика определения существенных настроечных параметров модели и методика оценки адекватности модели.

The task of the adjustment technology development on the real regional macroeconomic system for the simulation model, that is a modification of the world dynamics model, is considered in this paper. System dynamics methodology, the theory of experimental design, mathematical analysis and simulation are used to solve the problem. For the first time the adjustment technology of system dynamics simulation model on a real regional macroeconomic system was developed. This adjustment technology includes the following stages: construction of logic functions that reflect the causal relationships in the model, evaluation and correction of significant model parameters, evaluation of the model adequacy. For evaluation the adequacy of the model it is proposed to use the Gini and Theil coefficients. The usage of adjustment technology developed by the authors allows getting an adequate simulation model of regional macroeconomic system that can be used to forecast the processes of its development. This technology has been used to predict the development processes of Kharkov region. The estimated values for Gini and Theil coefficients for the period 2007-2010 equal to 0.034 and 0.023, respectively, indicating the reliability of simulation results and efficiency of the adjustment technology.
Keywords: масштабирование функций; вычисление коэффициентов; модель Форрестера; адекватность модели; коэффициенты расхождения Тейла; simulation model; forecasting; macroeconomic system; model adjustment; model adequacy